Increase in the Prevalence of Online Pornography Use: Objective Data Analysis from the Period Between 2004 and 2016 in Poland. - Lewczuk, Karol; Wójcik, Adrian; Gola, Mateusz (Archives of Sexual Behavior, 2022)
Despite the considerable amount of attention presently devoted to the high accessibility of online pornography, very little formal analyses have been carried out to show how the advent and proliferation of Internet technology has changed the prevalence of pornography use in populations. We conducted a preliminary analysis based on objective website traffic data, representing the changes in the number of (1) Internet users generally and (2) online pornography users specifically, between 2004 and 2016 in Poland. We observed a clear increase in the estimated number of people using online pornography in the analyzed period. The estimated number of general population members viewing pornography on the Internet increased over three times (310%) between October 2004 and October 2016–starting from an estimated 2.76 million in the first period to 8.54 million in the last. At the same time, we did not observe a clear increase in the percentage of Internet users who viewed online pornography in the same time period. Additionally, pornography viewership on the Internet was almost 2 times more prevalent among male (47%) than female Internet users (27%), and most popular in the 18–27 age group. Since our analysis is based on objective data, it does not share the limitations inherent in self-reports. However, our approach also has several important limitations (e.g., the analysis does not include online activity generated on mobile devices and under a private browsing mode); thus, the results should be interpreted with caution.